HOW INTELLECTUAL CAPITAL MEDIATES THE RELATIONSHIP BETWEEN PROFITABILITY, TAX AVOIDANCE, CAPITAL INTENSITY, AND FIRM VALUE - Joecelyn, Monica; Hiong, Lauw Sun (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2025)
ABSTRACTThe purpose of this study is to examine the effect of profitability, tax avoidance, and capital intensity on intellectual capital and on firm value. In addition, it also examines the mediating effect of intellectual capital on profitability, tax avoidance, and capital intensity on firm value. The population of the study was companies in the Property and Real Estate Sector on the IDX. The sample was selected using non-probability sampling, and a sample of 51 companies from 2019 to 2022 was obtained—data analysis using Multiple Regression Analysis. The study results show that return on assets positively affects intellectual capital. Tax avoidance and capital intensity do not affect intellectual capital. Profitability does not affect firm value, and intellectual capital positively affects firm value. Profitability positively affects firm value mediated by intellectual capital, while tax avoidance and capital intensity through intellectual capital cannot affect firm value. Stockholders can use the implications of the results of this study in preparing and taking investment policies because firm value is one of the indicators that can explain the company's financial performance holistically.ABSTRAKTujuan dari penelitian ini adalah untuk menguji pengaruh tingkat profitabilitas, tax avoidance, dan capital intensity terhadap intellectual capital dan terhadap nilai perusahaan. Selain itu juga menguji pengaruh mediasi intellectual capital terhadap profitabilitas, tax avoidance, dan capital intensity pada nilai perusahaan. Populasi penelitian adalah perusahan Sektor Property dan Real Estate di BEI. Sampel dipilih dengan non probability sampling dan diperoleh sampel sebanyak 51 perusahaan dari tahun 2019 -2022. Analisis data menggunakan Multiple Regression Analysis. Hasil penelitian menunjukan return on assets berpengaruh positif terhadap intellectual capital. Tax avoidance dan capital intensity tidak berpengaruh terhadap intellectual capital. Profitabilitas tidak berpengaruh terhadap nilai perusahaan dan intellectual capital berpengaruh positif terhadap nilai perusahaan. Profitabilitas berpengaruh positif terhadap nilai perusahaan dengan dimediasi intellectual capital, sedangkan tax avoidance dan capital intensity melalui intellectual capital tidak dapat mempengaruhi nilai perusahaan. Implikasi hasil penelitian ini dapat dihgunakan oleh stockholder dalam menyusun dan mengambil kebijakan investasi karena nilai perusahaan sebagai salah satu indikator yang dapat menjelaskan kinerja keuangan perusahaan secara holistik.